Effect of Precursor Solvent on the Carbon Micro-Structures Derived from Spray Pyrolysis of Pine Resin (Gondorukem): Preliminary Study - Jayadi; Widayatno, Wahyu Bambang; Wismogroho, Agus Sukarto; Firdharini, Cherly; Maddu, Akhiruddin; Alatas, Husin; Sari, Yessie Widya (Jurnal Sains Materi Indonesia, 2024)
Carbon materials have been widely used in various fields. This study aimed to produce carbon using spray pyrolysis with pine resin (gondorukem) as the precursor and different solvents, namely gondorukem-acetone (GAC), gondorukem-ethyl acetate (GEA), and gondorukem-dichloromethane (GDC). The precursor was prepared in a 1:8 (m/v) ratio, and the spray pyrolysis method was employed by heating the atomized precursor solution in the heating zone of a tube furnace. The atomization precursor was infused with nitrogen gas at a rate of 1 l/min with furnace temperature set at 1000°C with heating times of 5, 10, and 20 mins. The carbonaceous materials produced from the pyrolysis were collected on the wire mesh 1000 that was put on a stainless pipe. Carbon that has been coated on the wire mesh 1000 was analyzed using the optical microscope (OM). The physical properties and morphology of the synthesized carbonaceous material were analyzed using field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FTIR), Raman, and Brunaur-Emmett-Teller (BET). Based on FE-SEM analysis, the particle size of the GAC sample has an average of 283.58 nm and the highest carbon content, which reached an average of 97.312 At%. GAC samples had the lowest disorder properties in the Raman spectroscopy test, with the value of ID/IG reaching 0.795764. The functional groups observed were C–H stretching at 2920.49 cm-1, N–H bending at 1629.07 cm-1, and C–O stretching at 1159.70 cm-1. Based on carbon content, disorder properties, and functional group stabilization, carbon from the GAC precursor provides the ideal characteristics to be used as a filter material in medical masks. Meanwhile, based on BET testing, the carbon materials from GEA have the ideal material morphological properties to be used as a filter in medical masks. Spray pyrolysis is an efficient method for producing carbon materials, and the use of gondorukem as the precursor shows great potential for various applications.